2011
DOI: 10.1371/journal.pone.0016195
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Potentiates Glioma-Mediated Immunosuppression

Abstract: Glioblastoma multiforme (GBM) is a lethal cancer that exerts potent immune suppression. Hypoxia is a predominant feature of GBM, but it is unclear to the degree in which tumor hypoxia contributes to this tumor-mediated immunosuppression. Utilizing GBM associated cancer stem cells (gCSCs) as a treatment resistant population that has been shown to inhibit both innate and adaptive immune responses, we compared immunosuppressive properties under both normoxic and hypoxic conditions. Functional immunosuppression wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
141
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(144 citation statements)
references
References 55 publications
2
141
0
1
Order By: Relevance
“…It has been reported that hypoxia stimulates in tumor cells the release of immunosuppressive molecules (8)(9)(10), and more recently, that it increases lung cancer cell resistance to cytotoxic T-cell-mediated lysis (11). Other studies have focused on assessing the direct effect of hypoxia on the activity of innate immune effectors rather than on hypoxia-induced adaptations of tumor cells that might endow them with resistance to immunosurveillance (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that hypoxia stimulates in tumor cells the release of immunosuppressive molecules (8)(9)(10), and more recently, that it increases lung cancer cell resistance to cytotoxic T-cell-mediated lysis (11). Other studies have focused on assessing the direct effect of hypoxia on the activity of innate immune effectors rather than on hypoxia-induced adaptations of tumor cells that might endow them with resistance to immunosurveillance (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that pp65 is one of the major targets of the cellular immune response (16,17,23,24,49,59,61), and a long-term GBM survivor who underwent autologous dendritic cell vaccination was also found to mount a strong CD8 ϩ T-cell response to a pp65 immunodominant epitope (42). To assess both nucleotide and amino acid variability across the major pp65 epitope-producing domains, a 970-bp region of UL83 coding for amino acids 273 to 561 of pp65 was amplified and sequenced from seven tumor specimens that produced an amplification product (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Treated macrophages and microglia secreted immunosuppressive cytokines (IL-10, TGF-1, IL-23) and potentiated inhibition of T cell responses. Moreover, these functions were enhanced when glioma stemlike cells were cultured under hypoxic conditions (Wei et al, 2011). Overall, these studies suggest that glioma stem-like cells acquire their central role in tumour malignancy not only through their intrinisic stem-like properties and ability to thrive in hypoxic areas of the tumour, but also by recruiting myeloid cells, recently confirmed in vivo (Yi et al, 2011), and reinforcing their pro-tumoural effects.…”
Section: Microglia and Macrophage Function In The Contest Of Malignanmentioning
confidence: 58%